2022
DOI: 10.3847/psj/ac82aa
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Detectability of Europa’s Seafloor Topography from Europa Clipper’s Gravity Data

Abstract: Due to its size and tidal heating, Europa may potentially possess active volcanism and hydrothermal circulation at its seafloor. The upcoming Europa Clipper mission provides the opportunity to obtain global gravity maps over a range of spatial scales, up to degree l ≈ 10. We assess the ability of such gravity measurements to determine Europa’s seafloor topography, building on and extending previous work in this area. We create a suite of models that test the gravity signature of a wider range of possible topog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 29 publications
(40 reference statements)
1
13
0
Order By: Relevance
“…Without direct access to the surface of the body, the currently most viable way of probing the silicate interior consists in measuring its gravity anomalies. As shown in previous studies (Pauer et al 2010;Dombard & Sessa 2019;Koh et al 2022), the characteristic low rigidity of an ice shell, coupled with the elevated density contrast between the silicate mantle and the water ocean, results in the silicate interior dominating the total gravity field of the body at low degrees.…”
Section: Introductionsupporting
confidence: 52%
See 2 more Smart Citations
“…Without direct access to the surface of the body, the currently most viable way of probing the silicate interior consists in measuring its gravity anomalies. As shown in previous studies (Pauer et al 2010;Dombard & Sessa 2019;Koh et al 2022), the characteristic low rigidity of an ice shell, coupled with the elevated density contrast between the silicate mantle and the water ocean, results in the silicate interior dominating the total gravity field of the body at low degrees.…”
Section: Introductionsupporting
confidence: 52%
“…Here we describe a general structure for the interior of an icy body and detail the computation of the associated gravity potential. The modeling approach employed herein draws inspiration from the works of Koh et al (2022) and Pauer et al (2010). Unlike the aforementioned works, our focus lies on the gravitational potential rather than the surface acceleration produced by gravity anomalies.…”
Section: Generation Of a Gravity Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The final potentially confounding variable we consider is the gravity signature due to the core itself. Koh et al (2022) found that at Europa, core topography may dominate the gravity signal over that of ice-shell thickness variations up to degree-22. Given that Europa's diameter is 10 times larger than that of Enceladus and has a greater bulk density (∼3000 kg m −3 versus ∼1600 kg m −3 for Enceladus), the ratio of core mass to ice shell mass is much larger for Europa; therefore, the core's gravity signature would be much less significant in the case of Enceladus.…”
Section: Gravity Science Measurement Requirementsmentioning
confidence: 97%
“…Information on the thickness of Europa's ocean should give improved constraints on the ocean convection models described here and the relevant timescales. Gravity data from both JUICE and Europa Clipper can also help determine the seafloor topography or possible lateral compositional heterogeneity in the top part of the silicate interior (Koh et al., 2022), aiding in the characterization of bottom boundary conditions.…”
Section: Implications On the Structure And Evolution Of Icy Moonsmentioning
confidence: 99%